Modal Analysis Of UAV Aircraft Structures With Different Tail Configurations - Azlan, Nurul Aqmal Syuhaida (Universiti Sains Malaysia, 2017)
This thesis is to analyze the unmanned aerial vehicle aircraft structures using the modal analysis by using ANSYS Mechanical APDL software which requires an experienced student and the fundamental understanding of the ANSYS Mechanical APDL software. The three-dimensional beam element problems are considered to simplify the development which emphasizes on orderly procedure that involves the important element concepts such as natural frequency, and mode shape by using ANSYS Mechanical APDL result. The ANSYS’s ability to manipulate the design of the unmanned aerial vehicle with different configurations which makes the analysis more concise and easy to use. The flexibility of the Finite Element Analysis with ANSYS Mechanical APDL through the computer implementation allows most of the problems to be easily modified into design projects.